From public sphere to magic circle: playful publics on the Chinese internet. Issue 3 (2nd October 2021) - Xie, Emilie; Foxman, Maxwell; Xu, Shuo
Abstract: This paper reassesses comparisons of online Chinese networks to the Habermasian public sphere through a dialogue between sinology and ludology. Play has long been considered an integral component of public activity and of the Chinese internet. Researchers emphasised the importance of playful behavior and creative self-expressions for various purposes, including the formation of community ties and identities. However, studies tend to scrutinise the socio-political effects of playing rather than the fundamental connections between play and cultural life. This paper investigates the underlying cultural elements of play that are absent from or underdeveloped in the rational-critical framework and discourses of the public sphere. Building upon this ludological tradition, and specifically focusing on the autotelic, contextual, and appropriative nature of play, we conduct an exploratory, inductive thematic analysis of three case studies that garnered significant domestic and international attention – the abolishment of term limits in China, the #MeToo movement, and the COVID-19 pandemic – to understand the role of play in public communication. Our analysis reveals insights into the creative structural dynamics that underpin the Chinese internet – rules, reciprocity, and irrationality – three aspects that broaden discussions of online activity and engagement. The paper centers itself at the nexus of three separate strands of histories – the public sphere debate, ludology, and the Chinese internet – that have rarely been in dialogue with one another and, in doing so, examines and explains the Chinese cybersphere's current formation.